Effect of subcutaneous fat on long-term survival after surgery for stage I-III breast cancer as determined by computed tomography - Mao, Yi-Wen; Zeng, Hong-Dou; Fang, Ye; Wu, Xin-Yao; Zhang, Ming-Hao; Hu, Cheng-Da; Zhao, Ya-Xin (Frontiers in Oncology, 2025)
IntroductionMonitoring body composition through Computed Tomography (CT) scans, including muscle and adipose tissue, plays a key role in the prognosis of various cancers. However, abdominal CT is impractical for patients with breast cancer (BC), making chest CT an essential tool for postoperative surveillance. This study aims to evaluate the effect of subcutaneous fat tissue at the 11th thoracic vertebral plane on the postoperative prognosis of BC patients by analyzing chest CT images, providing evidence for postoperative nutritional and rehabilitation guidance.MethodsWe conducted a retrospective analysis of the medical records of 188 BC patients treated and discharged from the Second Affiliated Hospital of Wenzhou Medical University between January 1, 2013, and December 31, 2013. The subcutaneous fat area (SFA) at the 11th thoracic vertebra (T11) was measured using chest CT images, and the subcutaneous fat index (SFI, area/height2) was calculated. Using multivariate Cox proportional hazards models and propensity score matching (PSM), the relationships between the SFI and overall survival (OS), as well as recurrence-free survival (RFS), were assessed. Additionally, Kaplan-Meier survival curves were applied to compare prognostic differences between the groups.ResultsThe median follow-up duration was 128 months (range: 27-188 months). Of the 188 patients included in the study, the optimal cutoff value for the SFI was determined to be 49.31 cm²/m². Multivariate analysis indicated that SFI was an independent prognostic factor for both OS (HR 2.50, 95% CI 1.07-5.83, P = 0.034) and RFS (HR 2.04, 95% CI 1.10-3.78, P = 0.024). After PSM, Kaplan-Meier survival curve analysis revealed significant differences in both RFS and OS between the two groups (P = 0.025 and P = 0.018, respectively). All the results showed that the prognosis of BC with more subcutaneous fat was poor.DiscussionThe findings demonstrated that the SFI at T11 was negatively correlated with patient survival. This offers a new perspective on personalized management for BC patients, suggesting that future research should validate these results and investigate combining imaging assessments with lifestyle interventions, such as exercise, nutrition, and diet, to optimize patient outcomes.